Psalms for all seasons : a complete Psalter for worship - Witvliet, John D.; Tel, Martin; Borger, Joyce; Calvin Institute of Christian Worship (Grand Rapids, MI. : Faith Alive Christian Resources ; Grand Rapids, MI : Brazos Press, 2012)
This book is one of the most comprehensive resources on the Psalms for use in Christian worship. It covers the history, reception, and practice of psalm use and contains all 150 psalms, most in multiple formats. For each psalm, this volume includes: the complete New Revised Standard Version (NRSV) text of the psalm, presented with alternating regular and boldfaced type for responsive readings and red markings that enable the chanting of the psalm; a Christian prayer that responds to a theme, imagery, or basic intent of the psalm; a brief footnote which identifies the psalm's genre or type, highlights significant features of its form or imagery, and suggests a range of uses in Christian worship; one or more settings of the psalm, most of which are musical settings for congregational use. This range of material means that the book is well-suited to a variety of uses: corporate worship -- to be placed in the hands of worship leaders, choirs, and, ideally, all worshipers; daily prayer at morning, noon, evening, and/or night; personal and family devotion; a resource for Bible study; for preachers, as a commentary on the book of Psalms; to inspire composers in a wide range of cultures and traditions to imagine new, vital, and faithful ways of rendering psalms. Psalms for All Seasons is well suited for use in worship and practical theology courses. It is also an invaluable resource for churches of all traditions, assisting clergy, worship leaders and planners, and choirs in bringing the Psalms back into the heart of congregational worship. - Publisher.
Includes indexes.
Includes Psalms for the Revised Common Lectionary.
Keywords: Psalters; Psalms (Music); Sacred vocal music